2012
DOI: 10.1177/1076029611432744
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Soluble Thrombomodulin Levels in Cardioembolic Stroke

Abstract: Soluble thrombomodulin (sTM) has been proposed as a potential marker of ischemic stroke. Results from previous studies remain controversial among different populations. We performed an analysis of plasma levels of sTM in Thai patients with acute ischemic stroke and determined whether sTM levels correlate with stroke subtypes, severity, and risk factors. Ninety-three patients and 76 controls were enrolled. Blood samples were obtained within 24 hours after stroke onset. Plasma sTM levels, measured using quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
2
10
0
6
Order By: Relevance
“…A recent study reported that, in patients presenting with sepsis, sICAM-1 and sVCAM-1 were accurately associated with organ dysfunction and mortality, which is consistent with our observation [5]. Furthermore, in addition to luminal cell adhesion molecules, diffuse capillary injury and consequential coagulation disorders play an important role in the pathogenesis of sepsis [3,24]. As a marker of endothelial injury and coagulation, sTM may be used in monitoring organ dysfunction syndromes in septic patients [15].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study reported that, in patients presenting with sepsis, sICAM-1 and sVCAM-1 were accurately associated with organ dysfunction and mortality, which is consistent with our observation [5]. Furthermore, in addition to luminal cell adhesion molecules, diffuse capillary injury and consequential coagulation disorders play an important role in the pathogenesis of sepsis [3,24]. As a marker of endothelial injury and coagulation, sTM may be used in monitoring organ dysfunction syndromes in septic patients [15].…”
Section: Discussionsupporting
confidence: 88%
“…As such, TM is a central determinant of vascular endothelial thromboresistance by promoting anti-coagulant and anti-inflammatory properties within the vessel wall [1]. Shedding or release of soluble TM (sTM) into circulating blood has also been widely reported [2][5].…”
Section: Introductionmentioning
confidence: 99%
“…During endothelial pathologies, TM is released from the endothelium and can be detected in the serum in its soluble form. A significant increase in sTM level has been reported in vascular diseases, such as atherosclerosis, cardioembolic stroke, and sepsis-associated disseminated intravascular coagulation, indicating that sTM may represent a useful marker to assess endothelial dysfunction and vascular risk [22,23]. We also found increased levels of sTM in SCF subjects relative to controls, although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 48%